THE INFLUENCE OF ACADEMIC MANAGEMENT, STUDENT SATISFACTION, QUALITY OF SERVICE ON LEARNING INFORMATION SYSTEMS IN VOCATIONAL SCHOOLS - Chairunnisak (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to find out how much influence the variables of Academic Management, Student Satisfaction and Service Quality have on the Learning Information System, both simultaneously and partially. Quantitative research is a type of research that has systematic, planned and clearly structured specifications from the beginning to the end of the design. The total number of samples was 133 samples consisting of several Vocational High Schools in Kutacane. Academic Management has a positive and significant effect on the Learning Information System, Student Satisfaction has a positive and significant effect on the Learning Information System, Service Quality has a positive and significant effect on the Learning Information System. Then Academic Management, Student Satisfaction and Service Quality have a positive and significant effect on the Learning Information System.